Prosthodontic Implications Of Saliva On Denture Weares - Stavreva, Natasha; Georgievska Jancheska, Tatjana (International Organization of Scientific Research, 2024)
It is imperative for the dentist prosthodontist to give due attention to the salivary characteristics before, during and after denture fabrication. The fact that the teeth are in constant contact with and bathed by the saliva would suggest that this environmental agent could profoundly influence the state of oral health of a person. Denture retention is also to a large extent dependent upon saliva. Retention in complete denture prosthodontics is defined as the quality inherent in the prosthesis which resists the forces of dislodgement along the path of insertion. Successful rehabilitation of edentulous patients with complete dentures is largely contributed to by satisfactory denture retention. Saliva is a complex biological fluid that plays a very important role in maintaining the overall health of the oral cavity.